Attitudes of high school mathematics teachers in Jeddah towards teaching developed mathematics curricula - Al- Zahrani, Abdul Majeed Hussein; Al- Zahrani, Khaled Saeed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the attitudes of mathematics teachers at high school towards teaching developed mathematics curricula in Jeddah through identifying their attitudes towards: (nature- importance- enjoyment- courses and training programs for developed mathematics curricula as well as the suitability of the developed mathematics curricula with the capabilities of the student). It also aimed to identify the extent of having different attitudes among high school mathematics teachers towards teaching developed mathematics curricula according to the variables (type of qualification- years of experience) and the interaction between the study variables. The study followed the descriptive survey approach and was conducted on (174) mathematics teachers at high schools of the Jeddah City Education Department. The study reached a set of results, the most important of which are:-  Attitudes of high school mathematics teachers towards (the nature of developed mathematics curricula- the importance of developed mathematics curricula- the enjoyment of teaching developed mathematics curricula- training courses and programs- the suitability of the developed mathematics curriculum with the student's abilities) came to a high level.- There were no statistically significant differences in the study sample’s responses about the attitudes of mathematics teachers at high schools towards teaching mathematics curricula developed according to the variables (academic qualification- years of experience).Based on the study findings, the researcher recommended the following: the need to pay more attention to the training in the new mathematics curricula for mathematics teachers; working on providing all possible means to develop training and its methods because of its positive impact on teachers' attitudes towards curricula; developing teachers’ positive attitudes towards improved mathematics curricula by setting up enrichment programs to help mathematics teachers deal with the improved mathematics curriculum.
Keywords: Attitude; Teaching; Developed Mathematics Curricula